Atomic sizes and atomic properties - Ganguly, P. (Journal of Physics B-Atomic Molecular and Optical Physics, 2008)
We examine the dependence of atomic properties on a new atomic size, r(n)(Z)(c), that has been rigorously defined by the presence of an interaction without depending on the strength or nature of the interaction. We have thus related the static dielectric polarizability radius, r(alpha), the inverse of the first ionization potential, I(-1), the inverse of Pauling electronegativity scale, chi(-1)(P) and the size CR of atoms that contribute to interatomic distance involving atoms of the main group elements in the periodic table. There is a linear relationship between r(n)(Z)(c) and a size-dependent atomic property P of the form P = C(P)r(atom) + D(P), where r(atom) is a simple and transparent function of r(n)(Z)(c) and DP is simply related to the property of the hydrogen atom, except for P = I(-1) when DP is a property of the occupancy of the valence s-and p-electrons. We find a strict criterion for metallicity in elements based on atomic sizes and show how this criterion can be used to account for changes in descriptions of interatomic distance for gas-phase MX compounds of metallic elements.

Long-range synthon aufbau modules (LSAM) in crystal structures: systematic changes in C6H6-nFn (0 <= n <= 6) fluorobenzenes - Ganguly, P.; Desiraju, Gautam R. (Crystengcomm, 2010)
We discuss the assembly of a three-dimensional molecular crystal in terms of short-range supramolecular synthons that spontaneously organize themselves according to Aufbau principles into long-range geometries characteristic of the molecules themselves. For this purpose we have examined the systematic changes in the known crystal structures of a family of fluorobenzenes, C6H6-nFn, where 0 <= n <= 6. Crystal assembly is initiated by forming long-range synthon Aufbau modules (LSAM) that carry the imprint of the synthons. For example, when 1 <= n <= 5 the short-range synthons use H center dot center dot center dot F interactions to form the LSAMs. In the n = 0 and n = 6 compounds, the synthons are H center dot center dot center dot C and F center dot center dot center dot C interactions, respectively. The LSAMs are usually one-dimensional. In this study we show that these 1D LSAMs assemble into 2D quasi-hexagonal close-packed layers. The 3D crystal structure is obtained from the various kinds of close-packing known for these 2D layers. The final stages of this 1D -> 2D -> 3D assembly seem to be more influenced by the packing of LSAMs than by any other factor. In these final stages, there may not be so much influence exerted by the stronger short-range synthons. We discuss the evolution of these fluorobenzene crystal structures in terms of putative LSAMs and the purely geometric relationships between the n and (6 - n) compounds that can thus be expected. Such particle-hole pairs show structural similarities. Our discussion is quantified by the interpretation of intermolecular distances in terms of atomic sizes and with qualitative predictions of magnetic model systems.